Improving competitiveness of readymade garment (RMG) industry of Bangladesh - analysis of supply chains - Nuruzzaman, Md (Curtin University, 2013)
This study attempts to develop a model of improving competitiveness through analysing the supply chain (SC) of RMG industry in Bangladesh. The main objective of this study is to investigate the influence of external stakeholders’ of RMG SC to the demand side and supply side issues for improving competitiveness. Mixed method research is adopted in this study and data are analyzed by Partial Least Square-based Structural Equation Modelling. This study revealed that stakeholders have influence to improve competitiveness.